African American Girls Reframing Perceptions and Changing Experiences - Belgrave, Faye Z. (Advancing Responsible Adolescent Development, 2009)
The teenage years can be exciting for girls, as they develop into young women and anticipate their future. For some, however, this developmental stage may be tempered by increased risks for teen pregnancy, school failure, and some health problems. African American Girls: Reframing Perceptions and Changing Experiences explores not only the challenges and stressors confronting this unique population, but also the strengths and resiliencies used to meet them. Examining prevailing trends while avoiding simplistic generalizations, the book is both descriptive (e.g., explaining similarities and differences with girls of other ethnicities and African-American boys in critical areas) and useful (e.g., providing concrete guidelines for professionals working to support prosocial development and prevent risky behaviors). This unique volume: Addresses salient issues of self and identity. Examines crucial domains, such as relationships, achievements and expectations, and issues that have a major impact on health and well-being. Offers practical recommendations and resources for working with African-American girls during the period when life experiences and decisions are most likely to affect adult outcomes. Discusses the lives of girls from diverse families, communities, and circumstances. Explores the influences of family, peers, community, and cultural traditions. Features sample activities for promoting positive development. Includes quotations reflecting the perspectives of the girls in their own words. African American Girls is an essential resource for a wide range of professionals, including clinical, child, and school psychologists, counselors, therapists, and social workers. Whether one's specialty is prevention, intervention, education, or research, this book is a must-have volume.